Management Practices and Performance of Projects of Forum for Women Development in Kabale District Uganda - Dorothy, Kesiime; Agaba Moses; Siraj, Kaaya; Bosco, Turyasingura John (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
The study focused on project management methods and outcomes in Uganda. FOWODE instance in Kabale District. The study's primary goals were to determine the impact of internal controls on project performance in the Kabale district, the impact of human resource management on project performance in the Kabale district, and finally, the impact of planning on project performance in the Kabale district. Using the sample size determination table by Morgan and Krejcie (1970), 103 respondents were chosen as the sample size from a total of 140 respondents. This suggests that in the Kabale district, planning is statistically significant to project performance. The null hypothesis was thus disproved. The study's final finding for goal one was that financial controls and compliance are crucial for enhancing project performance. Improved internal controls will increase FOWODE's capacity to use resources efficiently, reduce waste, and provide expected results. Regarding the second goal, the study came to the conclusion that rewards methods should be in line with project objectives and staff values. Lastly, on objective three, It is essential to develop a clear project planning framework that outlines the project's objectives, goals, budget, timeline, and resource allocation.